2016
DOI: 10.1177/1040638716663251
|View full text |Cite
|
Sign up to set email alerts
|

Tissue localization, shedding, virus carriage, antibody response, and aerosol transmission of Porcine epidemic diarrhea virus following inoculation of 4-week-old feeder pigs

Abstract: We determined tissue localization, shedding patterns, virus carriage, antibody response, and aerosol transmission of Porcine epidemic diarrhea virus (PEDV) following inoculation of 4-week-old feeder pigs. Thirty-three pigs were randomly assigned to 1 of 3 groups for the 42-day study: inoculated (group A; n = 23), contact transmission (group B; n = 5), and aerosol transmission (group C; n = 5). Contact transmission occurred rapidly to group B pigs whereas productive aerosol transmission failed to occur to group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 13 publications
(14 reference statements)
5
48
0
1
Order By: Relevance
“…In this study, USA/KS/2013 isolate-inoculated pigs displayed fecal viral shedding primarily during the first two weeks with a peak at 5–6 DPI and fecal swabs that were positive for PEDV nucleic acid at 21 and 28 DPI in some pigs. Seroconversion was also noted at 14 DPI and reached a peak level at 21 DPI [22]. When the spike sequence of the USA/KS/2013 isolate was compared to the Taiwan PEDVPT isolate, we found that these two viruses share high sequence identity (99%).…”
Section: Discussionmentioning
confidence: 87%
“…In this study, USA/KS/2013 isolate-inoculated pigs displayed fecal viral shedding primarily during the first two weeks with a peak at 5–6 DPI and fecal swabs that were positive for PEDV nucleic acid at 21 and 28 DPI in some pigs. Seroconversion was also noted at 14 DPI and reached a peak level at 21 DPI [22]. When the spike sequence of the USA/KS/2013 isolate was compared to the Taiwan PEDVPT isolate, we found that these two viruses share high sequence identity (99%).…”
Section: Discussionmentioning
confidence: 87%
“…Therefore, an experimental design that mimics natural airborne transmission with a very low amount of virus inocula in a very low volume or by blocking the inocula entering the esophagus after IN spray, is needed. Lastly, relatively low levels of PEDV replication can be detected in tissue-resident porcine macrophages in vivo [74][75][76] and in porcine alveolar macrophages in vitro [55]. Macrophages likely play a protective role against infection while serving as a reservoir for replicating virus.…”
Section: Innate Immunitymentioning
confidence: 99%
“…L-1-tosylamide-2-phenylethyl chloromethyl ketone (TPCK)-treated trypsin and GCDCA were purchased from Sigma-Aldrich (St Louis, MO) and elastase from porcine pancreas was obtained from Promega (Madison, WI). For the isolation of an US PEDV strain, the day 4 intestinal contents from a pig inoculated with a stool sample from an Indiana farm with a PEDV outbreak in 2013 [33] were diluted in minimum essential medium (MEM) for 1:10 and filtrated using a 0.2 μm membrane filter. The prepared sample was inoculated to confluent Vero cells grown in the 6-well plates.…”
Section: Cells Viruses and Reagentsmentioning
confidence: 99%